The potential of South Sudan's national law on protection and assistance to IDPs - Beyani, C; Kulang, G; Mwebi, R (Refugee Studies Centre, University of Oxford, 2020)
South Sudan faces significant and complex humanitarian challenges but the recent drafting of a national IDP law reflects a renewed commitment to and vision for protecting its citizens.